Dietary nutritional profile and phenolic compounds consumption inschool children of highlands of Argentine Northwest - Rossi, María Constanza (2018)
The objective of this work was to assess dietary patterns and consumption of phenolic compounds from fruits and vegetables byschoolchildren of high altitude regions from northwest of Argentina. A nutritional survey including food-frequency consumption, 24-h dietary recall and anthropometric measurements was applied to 241 children from 6 to 12years old. The amounts of the different classes of phenolic compounds were established from Food Composition Tables available in phenol-explorer website. Statistics analyses were performed using IBM SPSS 20.0. Nutritional status assessment showed underweight (2.2%), low weight (12.7%), overweight (12.7%) and obesity (7.4%). Mean intake of phenolic compounds was 412mg/day. Most consumed foods were infusions and sugar products, consumption of vegetables, fruits and dairy products were low compared to recommendations for this age. Considering that polyphenols have protective health effects, its low consumption could be a risk of development of chronic non communicable diseases.